Response of the Green Alga Chlamydomonas reinhardtii to the DNA Damaging Agent Zeocin - Čížková, Mária; Slavková, Monika; Vítová, Milada; Zachleder, Vilém; Bišová, Kateřina (Cells, 2019)
DNA damage is a ubiquitous threat endangering DNA integrity in all living organisms. Responses to DNA damage include, among others, induction of DNA repair and blocking of cell cycle progression in order to prevent transmission of damaged DNA to daughter cells. Here, we tested the effect of the antibiotic zeocin, inducing double stranded DNA breaks, on the cell cycle of synchronized cultures of the green alga Chlamydomonas reinhardtii. After zeocin application, DNA replication partially occurred but nuclear and cellular divisions were completely blocked. Application of zeocin combined with caffeine, known to alleviate DNA checkpoints, decreased cell viability significantly. This was probably caused by a partial overcoming of the cell cycle progression block in such cells, leading to aberrant cell divisions. The cell cycle block was accompanied by high steady state levels of mitotic cyclin-dependent kinase activity. The data indicate that DNA damage response in C. reinhardtii is connected to the cell cycle block, accompanied by increased and stabilized mitotic cyclin-dependent kinase activity.
Keywords: DNA, Plant; DNA Breaks, Double-Stranded; Bleomycin; dvouřetězcové zlomy DNA; Caffeine; Cell Cycle Checkpoints; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; cytostatické látky; bleomycin; Mutagens; Chlamydomonas reinhardtii; DNA Replication; replikace DNA; DNA rostlinná; kofein; Cytostatic Agents; mutageny; kontrolní body buněčného cyklu